A comparative study of evacuation strategies for high-rise building via combination of stair and elevator based on computer simulation. (2016) - Ding, Yuanchun; Weng, Falu
The evacuation strategies for high-rise buildings via a combination of stair and elevator are investigated in this paper based on computer modelling and simulation. First, a hypothetical 20-floor building with staircase, elevator and a population of 800 agents is established by using the Pathfinder software. Then, based on the obtained model, 10 kinds of evacuation scenarios are designed. The simulations indicate that different combinations of stair and elevator can result in significant differences in the total evacuation times (TETs), and the shortest TET is achieved in the scenario that has half of the occupants on the upper-half part of the building evacuated by elevator, and the others evacuated by stairs. Furthermore, for the occupants on the top floor, the most efficient evacuation strategy is to use the elevator directly, however, which also results in the stairs between the upper two floors unused, and leads to the TET being lengthened.